Inventory management of surgical supplies and sterile instruments in hospitals: a literature review. Issue 2 (4th May 2019) - Ahmadi, Ehsan; Masel, Dale T.; Metcalf, Ashley Y.; Schuller, Kristin
ABSTRACT: Operating rooms are considered a significant revenue source, as well as the main source of waste and cost, among the hospital's departments. Any cost savings in operating rooms will have a broad financial impact. Over the last decades, many researchers and practitioners have conducted studies to deal with the issue of managing surgical supplies and instruments, which are highly affected by surgeons' preferences. The purpose of this article is to present an up-to-date review of research in the field of inventory management of surgical supplies and instruments. We have analysed the literature in a systematic manner and organised the identified papers into two groups: the papers that were published by scientific researchers and developed optimisation techniques and the papers that were published by practitioners and reported their observations of the current issues in the operating room. We also identify the future research directions leading to operating room inventory cost reduction.